CBCT: A Comprehensive Overview of its Applications and Clinical Significance in Dentistry - Simranjeet Baccher; Inderjit M. Gowdar; Yadavalli Guruprasad; Rajendra N. Solanki; Reeturaj Medhi; Mona J. Shah; Dhaval N. Mehta (Wolters Kluwer Medknow Publications, 2024)
This review provides a comprehensive overview of cone beam computed tomography (CBCT) in dentistry. It covers the basic principles, various applications, advantages, limitations, considerations, and future prospects of CBCT in the field of dentistry.